Genome-scale CRISPRi screen identifies pcnB repression conferring improved physiology for overproduction of free fatty acids in Escherichia coli - Lixia Fang; Xueyan Hao; Jie Fan; Xiaolei Liu; Yaru Chen; Lian Wang; Xiaoying Huang; Hao Song; Yingxiu Cao (Nature Communications)
Abstract Microbial physiology plays a pivotal role in construction of superior microbial cell factories for efficient biosynthesis of desired products. Here we identify that pcnB repression confers improved physiology for overproduction of free fatty acids (FFAs) in Escherichia coli through genome-scale CRISPRi modulation combining fluorescence-activated cell sorting (FACS) and next-generation sequencing (NGS). The repression of pcnB can enhance the stability and abundance of the transcripts of genes involved in the proton-consuming system, thereby supporting global improvements in membrane properties, redox state, and energy level. Based on pcnB repression, further repression of acrD increases FFAs biosynthesis by enhancing FFAs efflux. The engineered strain pcnB i-acrD i-fadR + achieves 35.1 g L−1 FFAs production in fed-batch fermentation, which is the maximum titer reported to date in E. coli. This study highlights the significance of uncovering hidden genetic determinants that confer improved microbial physiology for enhancing the biosynthesis of desired products.